Outcomes and vaccination patterns against COVID-19 in a cohort of sickle cell disease patients in the state of Rio de Janeiro - Claudia de Alvarenga Maximo; Jorge Francisco da Cunha Pinto; Fabiana Canedo Pinto; Patrícia Brasil (Hematology, Transfusion and Cell Therapy)
Background: Patients with sickle cell disease were presumed to be at high risk for severe COVID-19 outcomes due to their compromised immunity and chronic comorbidities. This study aimed to evaluate vaccination patterns, healthcare utilization, and clinical outcomes in a cohort of sickle cell disease patients during the COVID-19 pandemic in Rio de Janeiro. Methods: A total of 289 over 18-year-old patients from the Epidemiology and Donor Evaluation Study (REDS-III) Brazil sickle cell disease cohort were followed between January 2021 and August 2023. Sociodemographic data, emergency department visits, hospitalizations, mortality rates, and COVID-19 vaccination status were collected. SARS-CoV-2 infection was confirmed by reverse transcription polymerase chain reaction testing for symptomatic or hospitalized patients. Results: Of the participants, 89.2% completed the primary vaccination schedule, 62.2% received the first booster, 30% the second booster, and 4.1% completed all five doses. Emergency visits increased slightly during the pandemic but were primarily due to vaso-occlusive crises. Of the 119 patients tested for SARS-CoV-2, six were positive, presenting mild symptoms with no COVID-19-related deaths. Vaccination rates in the cohort were similar to those in the general population, with Oxford/AstraZeneca and Pfizer being the most used vaccines. Discussion: The findings suggest that COVID-19 infection was not a significant trigger for vaso-occlusive crises or severe disease outcomes. High vaccination adherence likely played a key role in preventing severe COVID-19, alongside other factors such as social isolation and herd immunity. However, the overlap between symptoms of vaso-occlusive crises and COVID-19 may have caused diagnostic challenges. Importantly, the low morbidity and mortality observed emphasize the protective effect of vaccines, despite the presence of thromboplastic activity and pro-inflammatory states inherent to sickle cell disease. Addressing vaccine hesitancy remains crucial, particularly as booster doses show declining adherence. Conclusion: COVID-19 had a limited clinical impact on this cohort, with no significant role in triggering vaso-occlusive crises or severe outcomes. High vaccination rates and potential environmental or biological factors may have contributed to this protective effect.